Imitators and Optimizers in Cournot Oligopoly - Burkhard C. Schipper (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
We present a formal model of symmetric n-firm Cournot oligopoly with a heterogeneous population of profit optimizers and imitators. Imitators mimic the output decision of the most successful firms of the previous round a la Vega-Redondo (1997). Optimizers play myopic best response to the opponents' previous output. The dynamics of the decision rules induce a Markov chain. As expression of bounded rationality, firms are allowed to make mistakes and deviate from the decision rules with a small probability. Applying stochastic stability analysis, we characterize the long run behavior of the oligopoly. We find that the long run distribution converges to a recurrent set of states in which imitators are better off than optimizers. This finding appears to be robust even when optimizers are more sophisticated. It suggests that imitators drive optimizers out of the market contradicting a fundamental conjecture by Friedman (1953).
Keywords: D21; C72; D43; L13; 330; imitation; myopic best reply; bounded rationality; profit maximization hypothesis; stochastic stability; learning; Stackelberg; Oligopol; Nichtkooperatives Spiel; Imitationswettbewerb; Betriebswirtschaftliches Ziel; Lernprozess; Beschränkte Rationalität; Theorie